Glycolysis Regulation to Maintain Blood Glucose Homeostasis - Salih, Karzan Jalal; Sabir, Dana Khdr; Abdoul, Hayman Jalal (Kurdistan Journal of Applied Research, 2022)
Carbohydrates are the major source of energy for the living cells, they are the first cellular constituents that synthesized during photosynthesis from carbon dioxide and water by green plants through absorption of sun light. To be used as source of energy, carbohydrates compounds should undergo series of enzymatic metabolic stages in the cell. Beside the energy productions, catabolism of carbohydrates provides different intermediates molecules for the synthesis of biomolecules like fatty acids, amino acids, DNA, and RNA. Among the three main examples of monosaccharide (i.e: glucose, galactose, and mannose), glucose is considered as the central molecule in carbohydrate metabolism that all the major pathways of carbohydrate metabolism relate to it. Glucose is also an essential component of cellular metabolism in maintaining carbon homeostasis. Liver has shown to play a key role in monitoring and stabilizing blood glucose levels, therefore, it can be considered as glucostate monitor. In this article, we will review the major metabolic pathways of carbohydrate metabolism, their biochemical role in cellular energy production, and latest development in the understanding in these fields. Also, we discuss about the factors that participate in regulation of blood glucose concentration. We believe understand these process is essential for control scarbohydrate-related human disorders.